Religion Teachers’ Strategies to Internalize Tolerance Values at Catholic and Islamic Schools in Bajawa Nusa Tenggara Timur - Nuha, Ulin; Arifin, Zainal; Kuswandari, Yuli; Razak, Ainun Ruzana Abdul (Jurnal Pendidikan Agama Islam, 2021)
This research discusses the internalization of tolerance values at two educational institutions in Bajawa, East Nusa Tenggara, namely Catholic Elementary School (Sekolah Dasar Katolik) Tanalodu or SDK Tanalodu and Islamic Elementary School (Madrasah Ibtidaiyah) Al-Ghuraba or MI Al-Ghubara. It used a qualitative approach. Data were collected through in-depth interview and observation. This research found the following results: first, the internalization of tolerance values at SDK Tanalodu and MI Al-Ghuraba, including: togetherness, mutual respect, love, help and mutual care. Second, the f teachers’ strategies in teaching religious tolerance, includes exemplary, habituation, appreciation, and warning, telling wisdom stories, and role playing. Third, the impact of internalizing of religious tolerance values at Catholic Elementary School Tanalodu and MI Al-Ghuraba can provide a dynamic space for teachers and students to communicate with each other and respect differences. The implication of this research is the importance of schools providing equal and fair services to teachers and students to practice their respective religions comfortably and freely.